Nursing Teachers' Perception of Role Strain: A Qualitative Study - Shohreh Kolagari; Mansoureh Zagheri Tafreshi; Maryam Rassouli; Amir Kavousi; Sharareh Kolagari (Golestan University of Medical Sciences, 2015)
Background and Objective: Role Strain refers to the felt difficulty in fulfilling expectations, complying with the role obligations and balancing the various dimensions of roles. Role strain is a subjective state of distress experienced. The aim of this study was to explain nursing teachers' perception of role strain. Material and Methods: This qualitative study was conducted in 2013, based on conventional content analysis. Using purposeful sampling, 21 nursing teachers were selected from schools of Nursing and Midwifery of the country. The data was collected through Semi-structured, in-depth interviews, and analyzed via content analysis using Granhiem and Landman (2004). The rigor and confirmability of the data were used by Guba and Lincoln criteria. Results: The data was summarized in sixteen subcategories and five main categories. Nursing teachers' perception about role strain was placed in following categories: Duty interference, Work Overload, Clinical teaching problems, Educational system problems and Students' problems. Conclusion: Given the work-related requirements and role obligations, we recommend that managers and health policy makers be careful about some protective strategies to reduce the role strain.